Phylogenetic, Expression, and Bioinformatic Analysis of the ABC1 Gene Family in Populus trichocarpa - Zhanchao Wang; Haizhen Zhang; Jingli Yang; Yunlin Chen; Xuemei Xu; Xuliang Mao; Chenghao Li (The Scientific World Journal)
We studied 17 ABC1 genes in Populus trichocarpa, all of which contained an ABC1 domain consisting of about 120 amino acid residues. Most of the ABC1 gene products were located in the mitochondria or chloroplasts. All had a conserved VAVK-like motif and a DFG motif. Phylogenetic analysis grouped the genes into three subgroups. In addition, the chromosomal locations of the genes on the 19 Populus chromosomes were determined. Gene structure was studied through exon/intron organization and the MEME motif finder, while heatmap was used to study the expression diversity using EST libraries. According to the heatmap, PtrABC1P14 was highlighted because of the high expression in tension wood which related to secondary cell wall formation and cellulose synthesis, thus making a contribution to follow-up experiment in wood formation. Promoter cis-element analysis indicated that almost all of the ABC1 genes contained one or two cis-elements related to ABA signal transduction pathway and drought stress. Quantitative real-time PCR was carried out to evaluate the expression of all of the genes under abiotic stress conditions (ABA, CdCl2, high temperature, high salinity, and drought); the results showed that some of the genes were affected by these stresses and confirmed the results of promoter cis-element analysis.